Differences in the Eruption Angle of Palatally Displaced Canines in Klinefelter Syndrome: a Retrospective Study on Panoramic Radiographs - Ahmed Abulwefa; Hrvoje Brkić; Zvonimir Kaić (University of Zagreb. School of Dental Medicine, 2017)
Objective: To investigate the eruption angle of maxillary canine in patients with Klinefelter syndrome (KS) in which high prevalence of palatally displaced canine anomaly (PDC) has been found by clinical assessment. Subjects and Methods: The sample consisted of 37 KS males aged 20-34 years (mean 27 years) and the control group which consisted of 78 healthy males aged 20-27 years (mean 23 years). A pioneer method was used to measure the eruption angle. It was based on determining the topographic construction of mandibular gonion line called GO-GO method on panoramic radiograph. Results: The mean of eruption angle was increased for 10.58° in the right side and 9.69 ° in left side in patients with KS compared to those in the control group. The difference of mesioangular inclination of palatally displaced canines in Klinefelter patients was statistically significant (p< 0.01). When eruption angle in the control group was compared to Klinefelter patients, the statistical difference was confirmed for respective sides (P <0.01 for both). Conclusions: The difference between eruption angle values in KS patients as well as in those belonging to the control group seemed to identify a developmental disturbance, thus confirming the fact that an extra X chromosome has an influence. The GO-GO method might be used for males when it is difficult to define occlusal planes, or for comparison. If this method is used, the eruption angular values should not exceed 56.74°.